2017
DOI: 10.1037/ocp0000043
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating teacher mindfulness: Effects of a randomized controlled trial on work, home, and sleep outcomes.

Abstract: The effects of randomization to a workplace mindfulness training (WMT) or a waitlist control condition on teachers' well-being (moods and satisfaction at work and home), quantity of sleep, quality of sleep, and sleepiness during the day were examined in 2 randomized, waitlist controlled trials (RCTs). The combined sample of the 2 RCTs, conducted in Canada and the United States, included 113 elementary and secondary school teachers (89% female). Measures were collected at baseline, postprogram, and 3-month foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
147
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(168 citation statements)
references
References 75 publications
15
147
1
5
Order By: Relevance
“…In health care providers, mindfulness training reduced burnout, mood disturbances, and stress (9,10). Mindfulness training also showed improvements in mood and sleep quality among teachers (11). …”
Section: Introductionmentioning
confidence: 99%
“…In health care providers, mindfulness training reduced burnout, mood disturbances, and stress (9,10). Mindfulness training also showed improvements in mood and sleep quality among teachers (11). …”
Section: Introductionmentioning
confidence: 99%
“…Roeser et al, 2013). This is also consistent with a number of previous studies in which participants observed that a general improvement in their perceived quality of life had a spill-over effect from work to home (Crain, Schonert-Reichl & Roeser, 2016;Singh et al, 2013;Soloway, 2011).…”
Section: Personal and Professional Benefitssupporting
confidence: 91%
“…Interestingly, in a number of studies, beneficial outcomes were not limited to interactions with students, but appeared to transfer across to close personal relationships (e.g. Crain, Schonert-Reichl & Roeser, 2016;Singh et al, 2013). This spill-over effect into the personal lives of teachers appears to create a compounding effect of the beneficial impact of mindfulness training on overall teacher well-being.…”
Section: The Benefits Of Mindfulness For Teachers -An Overviewmentioning
confidence: 99%
“…In our prior study with Information Technology (IT) workers, we found that employees whose managers were less supportive of work and family issues slept less. 14-16 Thus far, our prior study has demonstrated a positive effect of a workplace intervention for reducing WFC 17 on objective sleep outcomes within a randomized controlled trial. In a randomized experiment in an IT firm, the workplace intervention that addressed reducing WFC through an organizational change process significantly increased employees’ actigraphically-assessed total sleep duration and perceived sleep sufficiency.…”
Section: Introductionmentioning
confidence: 94%
“…18 This research points to the possible benefits of interventions aimed at increasing workplace and manager support as well as increasing employee's control over work time to improve employee sleep, and the need to investigate intervention effects in other settings such as health care. Limited research on workplace intervention effects on sleep has focused on individual-level employees’ coping behaviors, such as mindfulness practices, 17, 19 rather than organizational changes in work practices. A few studies, however, have suggested that it is critical to reduce WFC at the workplace level to enhance employee well-being, including sleep.…”
Section: Introductionmentioning
confidence: 99%